The association between healthy diet indicator and phytochemical index with prostate cancer odds ratio: a case-control study - Marzieh Mahmoodi; Farzaneh Mohammadi; Milad Rajabzadeh-dehkordi; Yahya Jalilpiran; Maede Makhtoomi; Mehran Nouri; Shiva Faghih (BMC, 2024)
Abstract Background and objective Healthy diets and diets rich in phytochemicals can have health-promoting benefits in prostate cancer. Therefore, this study aimed to explore the possible association between Healthy Diet Indicator (HDI) and Phytochemical Index (PI) with prostate cancer odds ratio. Methods This is a case-control study conducted in Shiraz, Iran, involving 62 newly diagnosed prostate cancer cases and 63 hospital-based controls. The study collected demographic and anthropometric data, as well as dietary intake information via a semi-quantitative food frequency questionnaire. Logistic regression models were employed to evaluate the association between HDI and PI with prostate cancer. Results The study included 120 participants and found that individuals with higher HDI and PI scores had a lower odds ratio of prostate cancer (HDI: odds ratio (OR): 0.322 - confidence interval (CI) 95%: 0.14-0.700 - PI: OR: 0.426 - CI 95%: 0.204-0.888). After adjusting for potential confounders, a lower odds ratio of prostate cancer was observed specifically among those with higher HDI scores (OR: 0.376 - CI 95%: 0.163-0.868). Conclusion The findings of the present study suggest that adopting healthier dietary habits rich in dietary phytochemicals could be effective in preventing and halting the progression of prostate cancer.